A newly recorded crab-spider genus Misumenoides F.O. Pickard-Cambridge, 1900 (Araneae: Thomisidae) from Khulna, Bangladesh (Journal of Biodiversity Conservation and Bioresource Management, 2021)
A study on the crab-spider genus Misumenoides F. O. Pickard-Cambridge, 1900 (Araneae: Thomisidae) was carried out in Khulna, Bangladesh. One species namely – M. deccanes Tikader was recorded for the first time from the present study area. Illustrated description and distribution of the species are provided together with generic diagnosis.J. Biodivers. Conserv. Bioresour. Manag. 2020, 6(1): 77-82